Pengaruh Model Pembelajaran Cooperative Integrated Reading And Composition (Circ) Terhadap Hasil Belajar Siswa Sekolah Menengah Atas - Hasriyanti, Hasriyanti (UNIVERSITAS NEGERI MAKASSAR, 2019)
This research aims to determine the differences geography with use Cooperative Integrated Reading and Composition (CIRC) with konvensional model in subject matter hidrosphere in Senior High School 3 Makassar. The study was a quasy experimental design involving two groups were taught using Cooperative Integrated Reading and Composition (CIRC) model and the group that wastaught using conventional learning models. The population in this study were all students of class X Senior High School 3 Makassar and sample are students of class X3 and X4 with purposive sampling. Technic data collection is done by giving a pre – test and post- test. The data were analyzed with descriptive and inferential techniques. Descriptive analysis showed that: (1) the study of students taught with conventional learning model gained an average score 65,25 Value obtained the percentage of students in the category of very less 0 % Category less 2.77 %, category 36.11 % enough , 61.12 % good category and the category of very good 0 %. (2) the study of students taught with Cooperative Integrated Reading and Composition (CIRC) learning model gained an average score 79,05 Value obtained the percentage of students in the category of very less 0% Category less 0 %, category 0 % enough , 88,57 % good category and the category of very good11,43 %. (3) According to the result is Thitung = 10.410 with Ttabel = 1,671 with the value α use the 0,05 (5 %) with df 69. Jadi Thitung < Ttabel, point to that P-value for t-test is 0,000. Hal ini berarti 0,000 < 0,05, maka H0 ditolak. Berdasarkan nilai signifikasnsi tersebut, maka dapat disimpulkan bahwa ada pengaruh yang signifikan terhadap hasil belajar geografi antara siswa yang belajar dengan model CIRC.